Moral Values in Five Novels by Syahid Muhammad and Their Suitability as Literature Teaching Materials in High Schools - Cahyo, Ahmad Nur; Nuryatin, Agus; Naryatmojo, Deby Luriawati (Universitas Negeri Semarang, 2023)
This research objective to explain the moral values and suitability of the five novels written by Syahid Muhammad for literature teaching materials in high school which can be seen based on the content of their moral values. The approach used is a pragmatic and structural approach as well as descriptive analysis. Research data was obtained through semiotic reading, namely heuristic reading. Data were analyzed using hermeneutics. This research obtained the results that the five novels by Syahid Muhammad contained three moral values, namely the moral value of human relationships with God, the moral values of human relationships with themselves, and the moral values of human relationships with other humans. Moral values that have a relationship between humans and God include prayer, gratitude, faith, piety, trust, and regret. Moral values that have a relationship between humans and themselves include honesty, responsibility, healthy living, discipline, hard work, self-confidence, entrepreneurial spirit, logical thinking, creative innovation, independence, curiosity and love of knowledge. Finally, there are moral values that relate to the relationship between humans and other humans, including caring for others, helping each other, deliberation, living in harmony, forgiveness, keeping promises, and respecting other people. The more dominant moral values are prayer, gratitude, honesty, logical thinking, creativity, innovation, caring for others, forgiveness, respect for others. Finally, the results of the analysis on five novels by Syahid Muhammad, it can be concluded that they have met the criteria as teaching materials because they meet the appropriate aspects of language, psychology and cultural background. So it can be concluded that the five novels by Syahid Muhammad can be used as a choice of literary teaching materials in high school.